2018
DOI: 10.1128/jcm.00149-18
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Colistin Resistance among Gram-Negative Rods and Klebsiella pneumoniae Isolates

Abstract: Infections due to colistin-resistant (Col) Gram-negative rods (GNRs) and colistin-resistant isolates in particular result in high associated mortality and poor treatment options. To determine the risk factors for recovery on culture of Col GNRs and Col, analyses were chosen to aid decisions at two separate time points: the first when only Gram stain results are available without any bacterial species information (corresponding to the Col GNR model) and the second when organism identification is performed but p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 37 publications
(71 reference statements)
4
27
1
Order By: Relevance
“…Previous estimates for colistin resistance prevalence have varied. In one study from a single academic medical center over a 6-year period using BMD, 0.45% of all Gram-negative rods (excluding isolates with intrinsic colistin resistance) showed a colistin MIC of Ն4 g/ml, and 1.5% of all K. pneumoniae had an MIC of Ն4 g/ml (36). In another study evaluating carbapenemresistant K. pneumoniae (CRKP) using broth macrodilution, 13% of CRKP had an MIC of Ն4 g/ml (37).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous estimates for colistin resistance prevalence have varied. In one study from a single academic medical center over a 6-year period using BMD, 0.45% of all Gram-negative rods (excluding isolates with intrinsic colistin resistance) showed a colistin MIC of Ն4 g/ml, and 1.5% of all K. pneumoniae had an MIC of Ն4 g/ml (36). In another study evaluating carbapenemresistant K. pneumoniae (CRKP) using broth macrodilution, 13% of CRKP had an MIC of Ն4 g/ml (37).…”
Section: Discussionmentioning
confidence: 99%
“…Gradient diffusion strips for colistin testing should not be used because of their high rates of very major errors. Reference BMD remains the gold standard, and some laboratories do use this method (36). Others have evaluated Sensititre Research Use Only GNX2F plates (Thermo Fisher, Waltham, MA) (41).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these mechanisms, the first plasmid-mediated colistin resistance gene, mcr-1, was identified on an IncI2 plasmid from Escherichia coli and K. pneumoniae in China [5]. Another plasmidmediated colistin resistance gene mcr-2 was found in 2016 [6]. It was suggested that dissemination of the mcr genes can lead to a serious escalation of the current antibiotic resistance crisis in the World [6].…”
Section: Introductionmentioning
confidence: 99%
“…It is serious as it concerns today antibiotics of last resort like colistin and carbapenems. This situation raises fears of reaching the tipping point, that is, a return to the preantibiotic era [11,12]. Senegal is not immune to this scourge in view of the results of the WHO JEE [18].…”
Section: Discussionmentioning
confidence: 99%
“…In the WHO African region, this resistance is detected in 57% of cases while in the WHO region of the Americas it is 100% [10]. Recently cases of colistin resistance have been reported in the United States [11] and China [12].…”
Section: Introductionmentioning
confidence: 99%